Analysis of Human Faecal Host Proteins: Responsiveness to 10-Week Dietary Intervention Modifying Dietary Protein Intake in Elderly Males - Gathercole, Jessica L.; Grosvenor, Anita J.; Lee, Erin; Thomas, Ancy; Mitchell, Cameron J.; Zeng, Nina; D'Souza, Randall F.; Ramzan, Farha; Sharma, Pankaja; Knowles, Scott O.; Roy, Nicole C.; Sjödin, Anders; et al. (Frontiers in Nutrition, 2021)
Faecal proteomics targeting biomarkers of immunity and inflammation have demonstrated clinical application for the identification of changes in gastrointestinal function. However, there are limited comprehensive analyses of the host faecal proteome and how it may be influenced by dietary factors. To examine this, the Homo sapiens post diet proteome of older males was analysed at the completion of a 10-week dietary intervention, either meeting the minimum dietary protein recommendations (RDA; n=9) or twice the recommended dietary allowance (2RDA, n=10). The host faecal proteome differed markedly between individuals, with only a small subset of proteins present in ≥ 60% of subjects (14 and 44 proteins, RDA and 2RDA respectively, with only 7 common to both groups). No differences were observed between the diet groups on the profiles of host faecal proteins. Faecal proteins were detected from a wide range of protein classes, with high inter-individual variation and absence of obvious impact in response to diets with markedly different protein intake. This suggests that well matched whole food diets with two-fold variation in protein intake maintained for 10 weeks have minimal impact on human faecal host proteins.